12x+9=9x-18

Simple and best practice solution for 12x+9=9x-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+9=9x-18 equation:


Simplifying
12x + 9 = 9x + -18

Reorder the terms:
9 + 12x = 9x + -18

Reorder the terms:
9 + 12x = -18 + 9x

Solving
9 + 12x = -18 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
9 + 12x + -9x = -18 + 9x + -9x

Combine like terms: 12x + -9x = 3x
9 + 3x = -18 + 9x + -9x

Combine like terms: 9x + -9x = 0
9 + 3x = -18 + 0
9 + 3x = -18

Add '-9' to each side of the equation.
9 + -9 + 3x = -18 + -9

Combine like terms: 9 + -9 = 0
0 + 3x = -18 + -9
3x = -18 + -9

Combine like terms: -18 + -9 = -27
3x = -27

Divide each side by '3'.
x = -9

Simplifying
x = -9

See similar equations:

| 4x-5=3-7x | | 48=4(x+10) | | 4u^2-4=15 | | 5v+7=6v-11 | | 6x=5x+16 | | 16(x+3)-4x=4(3x+2)-12 | | 5(3x-7)-(3x+9)= | | 19-u=238 | | -8(b-5)=-2(b+1) | | a-3[b-2(c-x)]=4 | | 167=2(3w-5)+2w | | 3x+6=9(x+4) | | 3(6p+5)=21 | | 3x+6=9(x+9) | | 7(4x+7)=6(1+x)-1 | | 2e^3x-2=7 | | C-13=5(3) | | 40=8(n-2) | | -5(8x+4)=-140 | | c=49.99-.25*49.99 | | 4[8-(-9x-1)]=180x+52 | | 3y-10x=-45 | | 5(4x-3)=15 | | x=(4y-9)(6y-7) | | 5+x=4(8) | | y+8=3(x+15) | | 70619.542=2*3.14*1303.21+2*3.14*36.1*h | | 2+4sinx=0 | | 422.67=c+.15c | | -(-4x+10-8y)= | | 8+3m-4=6m+9-2m | | 4x-5+x=7+5x-2 |

Equations solver categories